Parent reported outcomes of quality care and satisfaction in the context of a life-limiting fetal diagnosis. (18th April 2017) - Wool, Charlotte; Repke, John T.; Woods, Anne B.
Abstract: Objective: To identify which quality indicators (QI) predict patient satisfaction. Methods: A cross-sectional design using a validated tool was administered using a Web-based platform. Parents ( n  = 405) who experienced a life-limiting fetal diagnosis and opted to continue their pregnancy provided feedback on 37 QI and satisfaction with prenatal care. Descriptive analyses and logistic regression identified relationships among variables. Results: Parental satisfaction with care was 75.6%. Statistically significant differences in mean scores were reported with satisfied patients reporting higher agreement with quality indicators. Parents who were satisfied with their care had 1.9 times the odds of reporting that consistent care was provided (CI: 1.4–2.4, p  < 0.01), 1.8 times the odds of reporting compassionate care (CI: 1.4–2.5, p  < 0.01) and 1.8 times the odds that they received help to cope with their emotions (CI: 1.4–2.3, p  < 0.01). The model correctly predicted parent satisfaction 92% of the time. Conclusion: Provision of consistent prenatal care is an important quality indicator for this population of parents. The odds of securing satisfied parents increase when families are treated with compassion and given resources to help them cope with the emotionally devastating experiences associated with a life-limiting fetal diagnosis.